HAMLET - SHAKESPEARE, WILLIAM, 1564-1616 (HARLOW, ENGLAND PEARSON EDUCATION, 2008)
Classic / British EnglishHamlet is the Prince of Denmark. His heart is filled with sadness and pain. Why? Only his two best friends, Horatio and Marcellus, know the true reason. The new king, Claudius, murdered Hamlet
INGLÊS
INCLUI ATIVIDADES SOBRE O TEXTO.
Keywords: LINGUAGEM; INGLES; TEXTOS FACILITADOS; TEATRO INGLES; TEXTOS PARA INICIANTES; LIVRO